On sustainable development of organization - Myszewski, Jan M (Business process management journal, 2016)
Purpose – The subjects considered in this research paper form the basic prerequisites for improving the effectiveness of organizational development. The author assumes that the effectiveness of any process depends on the size of the reserve of capacity of the resources used in the process (for details, see Appendix). The purpose of this paper is to determine the conditions for the effectiveness of improvement projects. Design/methodology/approach – The author has constructed an algorithm (called ABC) to control the capacity of resources. With its help, the author defines the strategy for improvement in an organization. The basic principle of this strategy is continuous improvement, and tactics to control resources refers to the ABC algorithm. Findings – The author shows that continuous improvement is a prerequisite for the effectiveness of this strategy. It is shown that the features of this strategy reflect sustainable development of the organization. Along with the algorithm ABC, it forms a basis for the sustainable development strategy. The author shows conditions for effectiveness and explains how the strategy shapes the sustainable development of the organization. The author also explains why commitment of top management is necessary, what it is, and how it can benefit the organization. Practical implications – This effort is symbolized by the involvement of resources in projects conducted to improve organizational functions. The result of the capacity growth is increased ability to confront new challenges. Originality/value – The author claims that the strategy for sustainable development is shaping the conditions for a gradual increase in the capacity of the resources used in the improvement process. The growth in resource capacity in the repeatedly run improvement projects can serve as a model of organizational learning. The learning process requires effort.